2000
DOI: 10.1126/science.288.5473.2040
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a Global Climate Cycle on Population Dynamics of a Migratory Songbird

Abstract: Progress toward understanding factors that limit abundances of migratory birds, including climate change, has been difficult because these species move between diverse locations, often on different continents. For black-throated blue warblers (Dendroica caerulescens), demographic rates in both tropical winter quarters and north temperate breeding grounds varied with fluctuations in the El Niño Southern Oscillation. Adult survival and fecundity were lower in El Niño years and higher in La Niña years. Fecundity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
455
9
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(481 citation statements)
references
References 17 publications
(18 reference statements)
16
455
9
1
Order By: Relevance
“…A large variety of response types have been proposed, some of which are very complex (Stenseth et al 2002). In birds, climate change may influence demographic rates directly (Saether et al 2000;Sillett et al 2000), but more commonly it is linked to range shifts (Parmesan & Yohe 2003) or changes in breeding phenology. For instance, variation in climate change between wintering and nesting grounds may adversely affect arrival times in migratory birds (Forchhammer et al 1998;Brown et al 1999;Crick & Sparks 1999;Dunn & Winkler 1999), or the response of a non-migratory bird population may not match that of its prey (Visser et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of response types have been proposed, some of which are very complex (Stenseth et al 2002). In birds, climate change may influence demographic rates directly (Saether et al 2000;Sillett et al 2000), but more commonly it is linked to range shifts (Parmesan & Yohe 2003) or changes in breeding phenology. For instance, variation in climate change between wintering and nesting grounds may adversely affect arrival times in migratory birds (Forchhammer et al 1998;Brown et al 1999;Crick & Sparks 1999;Dunn & Winkler 1999), or the response of a non-migratory bird population may not match that of its prey (Visser et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Populations can be influenced by events that occur during the over-wintering, migration and breeding periods, and regulation can occur by a combination of mechanisms operating in one or more of these seasons (Sillett et al 2000). In a general two-season model, a migratory population will be at equilibrium when the per capita net breeding output (reproductionKmortality) during the breeding season equals the per capita mortality during the wintering season (Fretwell 1972;Sutherland 1996).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, several studies have shown that climate conditions and climate indices can influence the timing of migration and the distribution of migratory birds (Cotton, 2003;Forchhammer et al, 2002;Sillett et al, 2000). Among these variables, temperature was found to have a strong statistical correlation with bird distribution (Root, 1988;Root and Schneider, 1993).…”
Section: Introductionmentioning
confidence: 99%